2018
DOI: 10.1111/1365-2656.12915
|View full text |Cite
|
Sign up to set email alerts
|

The crab spider–pitcher plant relationship is a nutritional mutualism that is dependent on prey‐resource quality

Abstract: Nutritional mutualisms are one of the three major categories of mutualisms and involve the provision of limiting nutrients (resources) to one species by another. It was recently shown in laboratory experiments that two species of pitcher‐dwelling crab spiders (Thomisidae), Thomisus nepenthiphilus and Misumenops nepenthicola, increased capture rates of flesh flies (Sarcophagidae) for their host, Nepenthes gracilis. The spiders ambushed pitcher‐visiting flesh flies and dropped their carcasses into pitchers after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The observed strategy of P . nepenthophilus to breed in Nepenthes could represent a further case of mutualism (Lam & Tan, 2018, 2019), because frogs and tadpoles provide essential nutrients like nitrogen and phosphorus to the plant. The adult frogs leave their excrements, skin fragments, and egg capsules and the tadpoles produce feces and waste after consuming their yolk in the fluid of the pitchers.…”
Section: Discussionmentioning
confidence: 99%
“…The observed strategy of P . nepenthophilus to breed in Nepenthes could represent a further case of mutualism (Lam & Tan, 2018, 2019), because frogs and tadpoles provide essential nutrients like nitrogen and phosphorus to the plant. The adult frogs leave their excrements, skin fragments, and egg capsules and the tadpoles produce feces and waste after consuming their yolk in the fluid of the pitchers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the number of aphids was lower on traps near plants with guttation, possibly due to the increased abundance of natural enemies in plants with guttation. Interestingly, the numbers of mosquitoes were also approximately 40% lower on traps near plants with guttation, which could be due to the presence of Thomisidae spiders near the guttation drops, as these spiders are known to use mosquitoes as prey [54]. Finally, we would like to highlight that the manipulative assay was carried out at the end of the season, when guttation drops were almost completely absent in the field, to avoid the natural presence of guttation drops.…”
Section: Discussionmentioning
confidence: 99%
“…These spiders feed on visiting insects drawn to the pitcher-plants [ 34 , 36 ], and in some circumstances, the spiders increase pitcher-plant prey consumption by dropping consumed prey remains into the pitchers. Interestingly, two studies by Lim et al [ 34 ], and Lam and Tan [ 37 ] concluded that the type of association between crab spiders and pitcher-plants is environmentally context-dependent. Lam and Tan [ 37 ] demonstrated that T. nepenthephilus increased the prey capture rates of Nepenthes gracilis , offsetting the nitrogen loss from consumption by T. nepenthephilus , resulting in an overall net gain.…”
Section: Spider–plant Associationsmentioning
confidence: 99%
“…Interestingly, two studies by Lim et al [ 34 ], and Lam and Tan [ 37 ] concluded that the type of association between crab spiders and pitcher-plants is environmentally context-dependent. Lam and Tan [ 37 ] demonstrated that T. nepenthephilus increased the prey capture rates of Nepenthes gracilis , offsetting the nitrogen loss from consumption by T. nepenthephilus , resulting in an overall net gain. However, this benefit only occurs under conditions where prey availability is low and is ultimately lost when prey availability increases, switching from a positively facilitative to a parasitic interaction [ 37 ].…”
Section: Spider–plant Associationsmentioning
confidence: 99%